Hybrid stepwise external wrapping for type a acute aortic dissection with cerebral Malperfusion - Suematsu, Yoshihiro (J Cardiothorac Surg, 2021)
BACKGROUND: Acute aortic dissection (AAD) is a life-threatening condition which can lead to coronary, brachiocephalic or branch vessel malperfusion, as well as aortic valve insufficiency, or aortic rupture. Mortality of surgical treatment in high-risk or elderly patients with Type A AAD (TAAAD) still remains high, and treatment for such patients remains controversial. We report a successful treatment of TAAAD with a communicating false lumen in a 60-year-old man with acute hemi-cerebral malperfusion. CASE PRESENTATION: The ascending aorta was wrapped with stepwise external wrapping (SEW) procedure, and subsequent thoracic endovascular aortic repair (TEVAR) was successfully performed. The patient was discharged in good physical condition without any complications. CONCLUSIONS: Hybrid therapy with SEW and TEVAR with TAAAD associated with major cerebral malperfusion should be considered, especially in patients for whom open surgery is extremely risky.